PMM.67 Screening for gestational diabetes using serial random blood glucose testing; the experience of a tertiary London unit. (9th June 2014) - Currie, JLD; Mustapha, A; Chambers, A; Dolan, M; Anderson, J; Dorman, E; Erskine, KJ; Parisaei, M
Abstract : Background: Best practice for screening for gestational diabetes (GDM) remains controversial. 1 In our tertiary London hospital women with risk factors for gestational diabetes undergo random blood sugar (RBS) testing at every visit. If raised they undergo 75g oral glucose tolerance testing (OGTT). This replaces single OGTT around 28 weeks, an alternative common practice. We hypothesise that this allows diagnosis of GDM whenever it develops, to optimise timely interventions. Method: Retrospective audit of women with diabetes in pregnancy at a tertiary London hospital. Data was extracted for March 2012 to March 2013 (5735 deliveries) to compare demographics, treatments and outcomes for GDM women diagnosed below 24 weeks, between 24 to 32 weeks and after 32 weeks (Table 1 ). Results: 124 women with new-onset diabetes in pregnancy were identified: 29 diagnosed before 24 weeks, 45 between 24–32 weeks, and 50 after 32 weeks. Conclusions: There appear to be differences between the groups, particularly regarding treatment with insulin, delivery before 37 weeks, and birthweight >4kg. Compared with single OGTT around 28 weeks, serial RBS may have allowed early diagnosis for 29/124(23.4%) women diagnosed before 24 weeks, and avoided missing diagnosing 50/124(40.3%) women diagnosed after 32 weeks. Reference: Waugh N, Royle P, Clar C, Henderson R, Cummins E, Hadden D, Lindsay R, Pearson D. Screening for hyperglycaemia in pregnancy: a rapid update for the National Screening Committee. Health Technology Assessment 2010;14(45)